The perfect siesta - Mena, Pato, 1980- (Colección somos8., 2017)
Even though he has something urgent to do, a jaguar decides to take advantage of a cool breeze to take a nap, so he asks the coati to wake him in exactly ten minutes, but the coati decides to take a nap too and asks another animal to wake him.